2017
DOI: 10.1038/s41467-017-01380-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic actuation and feedback cooling of a cavity optomechanical torque sensor

Abstract: Cavity optomechanics has demonstrated remarkable capabilities, such as measurement and control of mechanical motion at the quantum level. Yet many compelling applications of optomechanics—such as microwave-to-telecom wavelength conversion, quantum memories, materials studies, and sensing applications—require hybrid devices, where the optomechanical system is coupled to a separate, typically condensed matter, system. Here, we demonstrate such a hybrid optomechanical system, in which a mesoscopic ferromagnetic n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…This provides the ability to perform exquisitely sensitive optical measurements, with sub-attometre precision 8 . At kilometre scales it has proved crucial for the successful detection of gravitational waves 9 ; while at micro- and nano-scales it has enabled high-performance acceleration, single-molecule, temperature and magnetic field sensing 13,1013 , as well as provided a new approach to control the quantum physics of massive objects, allowing quantum ground-state cooling 1416 and the generation of macroscopic non-classical states of motion 17,18 , with applications in future quantum technologies (for e.g., see 1921 ).…”
Section: Introductionmentioning
confidence: 99%
“…This provides the ability to perform exquisitely sensitive optical measurements, with sub-attometre precision 8 . At kilometre scales it has proved crucial for the successful detection of gravitational waves 9 ; while at micro- and nano-scales it has enabled high-performance acceleration, single-molecule, temperature and magnetic field sensing 13,1013 , as well as provided a new approach to control the quantum physics of massive objects, allowing quantum ground-state cooling 1416 and the generation of macroscopic non-classical states of motion 17,18 , with applications in future quantum technologies (for e.g., see 1921 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical devices are independent of the waveguide elements to remove any size restrictions waveguide criteria would place on them. When used as a sensor, the separate optical and mechanical components also allow the mechanical sensor to contain metal features without causing significant optical losses due to unwanted plasmonic interactions [52]. The ∂T opt /∂λ at the probe location is directly proportional to the signal, and plotting their normalized dc optical transmission curves in sensitivity enhancement provided by optomechanics has unleashed new opportunities for studying fundamental physical properties.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…The feedback-cooled modal temperature as determined by fitting to the blue trace is T = 12 K. (Figures from Refs. [109,52], used with permission.) tal mode volume on the order of one cubic wavelength.…”
Section: Measurements With Photonic Crystal Cavity Readoutmentioning
confidence: 99%
“…The torque along the y-axis was induced by a magnetic field along the z-axis. As a magnetic field sensor, a linear responsivity of 0.134 ± 0.003 rad/mT and a detection limit of 150 nT were obtained [248]. Du et al [249] demonstrated a magnetic field sensor based on a pair of suspended coupled PhC nanobeam cavities.…”
Section: Torque/magnetic Field Sensormentioning
confidence: 99%